THE PEOPLE REPUBLIC OF CHINA'S FOREIGN POLICY TO SUCCEED 2008 BEIJING OLYMPICS GAMES (Case Study: Boycott Action toward 2008 Beijing Olympics Games) - Syarifah Deti Mashitah (2009)

(untitled)
Abstract The last Summer Olympics Games was held in Beijing from August 8th to August 24th, 2008. Unfortunately, before the Olympics Games was held, there were many boycott actions. There were two issues related to the boycott actions; human right violation in Tibet and environment issue. Pro Tibetan Activists and some dominant states claimed that The Summer 2008 Olympics Games couldn't be held in Beijing because the Government of China had devastated the main identities of Tibet, namely tradi